Implementasi Artificial Intelligence (AI) di Bidang Pendidikan Kejuruan Pada Era Revolusi Industri 4.0 - Muhammad Yahya; Wahyudi; Akmal Hidayat (SEMINAR NASIONAL DIES NATALIS 62, 2023)
Artificial Intelligence (AI) is a concept closely related to technological advancements in the era of Industry 4.0 and Society 5.0. AI can be described as a computer program that involves integrated machine learning, hardware, and software components. This concept of AI is inspired by the neocognitron patterns in the human brain and utilizes knowledge from hardware and software to fulfill its functions. With the progress of Industry 4.0, AI has been widely employed in various fields, including vocational education. The aim of this research is to elucidate the role of AI in vocational education during the Industry 4.0 era, utilizing qualitative research methods. In the context of vocational education, AI is used to personalize learning for each learner. AI systems assist in creating customized learning profiles, such as practical exercises, for individual learners. This enables the adaptation of learning materials to align with the abilities, learning styles, and experiences of each learner. The implementation of AI technology in vocational education is considered to be helpful and facilitates the tasks of educators, particularly in administrative aspects such as assessment and determining final grades based on applicable weights and evaluations. Additionally, AI technology can also create more active and interactive learning experiences, thereby facilitating the teaching and learning process for both educators and learners to achieve their goals.